A221 OPTIMAL PROCEDURAL SEQUENCE FOR SAME-DAY BIDIRECTIONAL ENDOSCOPY WITH SEDATION: A SYSTEMATIC REVIEW AND META-ANALYSIS STUDY OF CONTROLLED TRIALS. (15th March 2019) - DINARY, F; Busbaih, A; Khan, K
Abstract: Background: Same-day bidirectional endoscopy (BDE) is a commonly performed procedure, but the optimal sequence for the procedure is not well established. Aims: This study aimed to assess if upper endoscopy before colonoscopy was better than the opposite sequence. Main outcome measures were time of procedure, sedation used, recovery time, and quality of procedure. Methods: To conduct a systematic review and meta-analysis of controlled trials of moderate sedation that compared the sequence of combination procedures. Search strategy up to 2018 was conducted and relevant papers retrieved for analysis. All data was extracted as per-protocol by 2 reviewers in a double-blind fashion and discrepancies resolved by a third person adjudicator. Data were pooled where possible to get a summary effect. Results: Seven studies (N=1974 patients) were included. There were 6 randomized controlled trials, and 1 prospective cohort study with tandem procedures. None of the studies were from North America. Time of procedure was similar for upper endoscopy and colonoscopy regardless of which was done first, and there was no difference in the total time (Mean difference -0.04 minutes [-0.64, 0.56 p=0.89]). Three studies (N=455) reported recovery time was significantly better in the endoscopy first group (Mean difference -4.42 minutes [-5.26, -3.58]). Sedation data could not be statistically combined due to heterogeneity, but a clear trend suggested higher sedation was used in the colonoscopy first group. Limitations: marked variability in designs, protocols for sedation, and poor methodologic quality of most studies. Conclusions: Bidirectional endoscopy is a common procedure in gastroenterology, and the optimal sequence remains controversial. Starting with upper endoscopy does not reduce procedure times, but may reduce the amount of sedation and consequently, the recovery time. These findings may represent a subtle, but meaningful difference for patients and endoscopy units to consider. Funding Agencies: None